Competitiveness of Indonesia's Agricultural Exports To China: Trends and Strategic Insights - Novianti, Tanti; Sari, Anggi Mayang; Sari, Linda Karlina; Asikin, Zenal (Jurnal Manajemen dan Agribisnis, 2024)
Background: Economic development in open economies like Indonesia was marked by international trade. Starting with the restoration of diplomatic relations in 1990, China emerged as one of the biggest trading partners for Indonesia. However, Indonesia's competitiveness in the international market remained at a concerning level compared to other major exporters.Purpose: The research was conducted on the competitiveness of Indonesia's agriculture exports to China during 2019-2023, for certain commodities, and described Indonesia's current market position and growth prospects.Design/Methodology/Approach: The paper applied the Revealed Comparative Advantage and the methodologies of Export Product Dynamics in order to judge Indonesia's competitive position in major agricultural products, such as coconut, cashew nut, Brazil nut, coffee, nutmeg, cardamom, palm oil, copra, and natural rubber.Findings/Result: The analysis showed that nutmeg and cardamom showed outstanding growth, placing them in the "Rising Stars" status in the Chinese market, as evidenced by their high export share growth coupled with a high increase in global market share. On the other hand, palm oil and copra recorded negative competitiveness, leading into the "Retreat" quadrant.Conclusion: The study suggested that to build Indonesia's competitiveness in agricultural exports, it was important to improve quality and value addition through processing, besides non-tariff barrier understanding. These strategies would further fortify Indonesia's market position and trade performance at large with China and globally.Originality/value (State of the art): For the first time, this research performed updated research on agri-food products export competitiveness of Indonesia to the Chinese market, by using updated data availability (2019-2023) and combined methodology approach between RCA and EPD. The obtained insights would be very important guidance for policymakers in the formulation of endorsing better trade policies in agricultural commodities within Indonesia to increase its presence in world markets. Keywords: agricultural commodities, business analytics, business policy, market position, international trade